Communicating about raising the retirement age using frames and counterframes. Issue 2 (2nd May 2017) - Vyncke, Bart; Van Gorp, Baldwin
Abstract : Purpose: This study discusses the frames that were used in the public debate about raising the retirement age in Belgium from 65 to 67 years. The purpose of this paper is to gain insight into the prevailing frames in order to develop counterframes that are less problematizing and can be used to bring more nuance to the debate. Design/methodology/approach: An inductive framing analysis was conducted, using articles from Flemish newspapers and magazines, published in a two-year period (March 2013-March 2015). This sample was complemented by a convenience sample of texts by various stakeholders. The total sample consisted of 182 texts. Findings: The analysis yielded four problematizing frames and six deproblematizing counterframes. They cover both the meaning of work for the individual, and the effect that working longer has on society. Practical implications: The overview of the frames can be used as a tool to analyze existing communication, and to bring more nuance to future communication by introducing deproblematizing perspectives into the debate regarding the need to work for a longer period of time. Originality/value: In addition to giving an overview of existing frames, the study also constructed alternatives which can be used to deproblematize the issue of having to work longer.